Ecotoxicological evaluation of a fish farming effluent treated by Fenton oxidation and coagulation process. Issue 16 (1st November 2020) - Gomes, Lúcio M.; Silva, Jaqueline M.; Duarte, José L. S.; Tavares, Mariana G.; Santos, Elton L.; Machado, Sonia S.; Tonholo, Josealdo; P. S. Zanta, Carmem L.
ABSTRACT: This study has evaluated the efficiency of Fenton process followed by coagulation to treat real effluent from fish farm. Fenton obtained Chemical Oxygen Demand and turbidity removal of 48% at (0.5 mg L −1 Fe 2+ and 10 mmol H2 O2 ). Fenton followed by coagulation reduced COD and turbidity by almost 100%. The process also decreased the concentrations of suspended solids, phosphate, nitrate, Biological Oxygen Demand, and nitrite. Ecotoxicology test indicated that the effluent treated with 0.5 mmol L −1 Fe 2+ in 10 mmol L −1 H2 O2 displayed the lowest toxicity. These findings can indicate an environmental friendly alternative to treat fish farm effluent.